Kajian Kritis Akuntansi Sumber Daya Manusia Di Indonesia - Gotama, Go, Novia Amelinda Gotama; Mardatillah (STIE Madani Balikpapan, 2024)
Human resource accounting is a complex field involving not only financial aspects but also complex behavioral dimensions. The research method used is library research. This research aims to examine in more depth human resource accounting in Indonesia. This study tries to explain the differences in research results based on 15 previous research journals regarding human resource accounting. Through in-depth literature studies based on various relevant literature, this research tries to examine various previous research journals in Indonesia. The research findings provide insight that the use of human accounting resources in Indonesia has not been implemented in accordance with PSAK. However, human resource accounting also proves that the application of this theory can have a positive impact on company performance and the collection of company information.